2005
DOI: 10.1158/1055-9965.epi-04-0640
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation Spectrum in Lung Cancer Is Not Different in Women and Men

Abstract: Whether women are more susceptible to lung cancer than men has been controversial. Several case-control studies suggested that women have greater risk of lung cancer compared with men at similar levels of cigarette smoking, whereas some large cohort studies failed to observe this association. Other studies indicated that lung cancer may have biological characteristics and mechanisms of carcinogenesis that are gender specific. Therefore, we hypothesized that women are more susceptible to the carcinogenic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…Fourteen polymorphisms in TP53 were genotyped in two study populations, an ongoing case-control study (25,26) and a case-only study described previously (24,34). No variation was observed for TP53_25 (Ex11 +567, G>A) or TP53_64 (Ex6 À24, G>A) in our case-control or case-only study (data not shown).…”
Section: Resultsmentioning
confidence: 61%
“…Fourteen polymorphisms in TP53 were genotyped in two study populations, an ongoing case-control study (25,26) and a case-only study described previously (24,34). No variation was observed for TP53_25 (Ex11 +567, G>A) or TP53_64 (Ex6 À24, G>A) in our case-control or case-only study (data not shown).…”
Section: Resultsmentioning
confidence: 61%
“…This suggests that women may be more susceptible to the DNA damaging effects of tobacco smoke than men. Some, 28 31 32 but not all, 33 studies also identified sex differences in the frequency of mutations in tumour suppressor genes, with higher frequencies seen among women than men. Furthermore, it may be that women extract a greater quantity of carcinogens and other toxic agents from the same number of cigarettes than men, which again might explain why smoking confers a greater excess risk in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific differences have also been observed for associations between EGFR mutations and the HLA-A2(þ) allele. 24 In addition, p53 transversion mutations 25 and insertion/deletion mutations 26 are more frequent in females. Various carcinogens originated from environmental exposures or endogenous processes constantly threaten DNA integrity.…”
Section: Discussionmentioning
confidence: 99%